Nonsurgical Rhinoplasty: A Modified Rino-4-Puntos Technique With Hyaluronic Acid Improves the Appearance of Nasal Septal Deviation - Fernando Silikovich, MD; George Kroumpouzos, MD, PhD, FAAD (Plastic and Reconstructive Surgery, Global Open)
Background:. Recently, we introduced the Rino-4-Puntos (R4P) nonsurgical rhinoplasty technique using hyaluronic acid (HA), which effectively addresses nose shape issues. However, no nonsurgical rhinoplasty procedure has been explicitly tested for improving the appearance of nasal septal deviation (NSD). This study aimed to evaluate the aesthetic outcome, longevity of results, safety, and patient satisfaction of the modified R4P (mR4P) technique, designed to address nose shape issues related to NSD. Methods:. This was a retrospective study of consecutive patients treated with mR4P. NSD is the leading cause of unpleasing aesthetics. The R4P technique involves targeted injections with an intermediate G prime (G′) HA at the radix (point 1), supratip (point 2), and tip (point 3), and high G′ HA at the columella (point 4). To specifically address nose shape issues caused by NSD, modifications were made to points 4.2 and 4.3 of the technique. At these points, the needle insertion point was repositioned to the side of deviation. Then, the needle was directed diagonally opposite the deviation toward the nasal tip. Results:. Eighty individuals (68.7% women) were included. The procedure is suitable for mild-to-moderate caudal NSD, including I- and C-shaped NSDs. Notably, 87.5% of the participants were very satisfied and 12.5% were satisfied with the aesthetic outcome. Most (81.2%) patients reported respiratory improvements after mR4P. The treatment effect lasted for a median of 11 months. No vascular complications occurred. Conclusions:. The mR4P technique improves the appearance of caudal NSD and provides good longevity of the aesthetic outcomes and safety.